Calorimetric Monitoring of the Sub-Tg Crystal Growth in Molecular Glasses: The Case of Amorphous Nifedipine - Svoboda, Roman (Molecules (Basel, Switzerland), 2025)
Non-isothermal differential scanning calorimetry (DSC) and Raman microscopy were used to study the crystallization behavior of the 20-50 μm amorphous nifedipine (NIF) powder. In particular, the study was focused on the diffusionless glass-crystal (GC) growth mode occurring below the glass transition temperature (Tg). The exothermic signal associated with the GC growth was indeed directly and reproducibly recorded at heating rates q+ ≤ 0.5 °C·min-1. During the GC growth, the αp polymorphic phase was exclusively formed, as confirmed via Raman microscopy. In addition to the freshly prepared NIF samples, the crystallization of the powders annealed for 7 h at 20 °C was also monitored-approx. 50-60% crystallinity was achieved. For the annealed NIF powders, the confocal Raman microscopy verified a proportional absence of the crystalline phase on the sample surface (indicating its dominant formation along the internal micro-cracks, which is characteristic of the GC growth). All DSC data were modeled in terms of the solid-state kinetic equation paired with the autocatalytic model; the kinetic complexity was described via reaction mechanism based on the overlap of 3-4 independent processes. The kinetic trends associated with decreasing q+ were identified, confirming the temperature-dependent kinetic behavior, and used to calculate a theoretical kinetic prediction conformable to the experimentally performed 7 h annealing at 20 °C. The theoretical model slightly underestimated the true extent of the GC growth, predicting the crystallinity to be 35-40% after 7 h (such accuracy is still extremely good in comparison with the standard kinetic approaches nowadays). Further research in the field of kinetic analysis should thus focus on the methodological ways of increasing the accuracy of considerably extrapolated kinetic predictions.
Keywords: DSC; Raman microscopy; amorphous nifedipine; kinetic prediction; GC growth